First evidence of a lake at Ancient Phaistos (Messara Plain, South-Central Crete, Greece): Reconstructing paleoenvironments and differentiating the roles of human land-use and paleoclimate from Minoan to Roman times. (August 2018) - Ghilardi, Matthieu; Psomiadis, David; Andrieu-Ponel, Valérie; Colleu, Maxime; Sotiropoulos, Pavlos; Longo, Fausto; Rossi, Amedeo; Amato, Vincenzo; Gasse, Françoise; Sinibaldi, Laetitia; Renard, Mélanie; Bicket, Andrew; et al.
Phaistos was one of the most important Minoan palaces in Crete and previous studies have addressed its relationship with the paleo-seashore position during historical times. Here, we reconstruct the environmental evolution of Phaistos from Early Minoan to Roman times. Study of two stratigraphic sections and nine boreholes drilled in the westernmost part of the Messara Plain has revealed the stratigraphy of the Mid- to Late-Holocene sediments. Laboratory analyses comprise granulometry, magnetic susceptibility measurements and identification of mollusks, diatoms and pollen grains. Eighteen radiocarbon dates provide a robust chronostratigraphy. In addition, a geophysical survey (electric resistivity tomography (ERT) method) was conducted to reveal the sub-surface morphology in the coring area. The results reveal that a freshwater lake existed from ca. 2100–2000 BC to ca. 1200–1100 BC, which subsequently became swampland until ca. 700 BC. A lake retreat is identified at ca. 1200–1000 BC and can be interpreted as resulting from the 3.2 cal kyr BP rapid climate change (RCC) dry event, observed elsewhere in the Eastern Mediterranean. Subsequently, from the 7th to the 5th century BC, there was the input of detrital material and fluvial dynamics prevailed until at least Roman times. The origin of the lake and its disappearance are discussed in the context of regional climate change and local tectonic activity, without excluding possible human influences. We also reconstruct the vegetation history for the period from the Late Minoan to the Early Archaic period. Pollen analysis reveals a Mediterranean maquis landscape dominated by Olea, together with hygrophilous vegetation, and highlights a clear transition from limnic to swampy environmental conditions around 1100 BC. The pollen sequence is also important for assessing the impact of the 3.2 cal. kyr BP RCC event and for assessing the possibility of an abrupt discontinuity in human activity around Phaistos after the demise of the Minoan Civilization.